2019
DOI: 10.1038/s41541-018-0094-0
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming the adjuvant properties of aluminum oxyhydroxide with nanoparticle technology

Abstract: Aluminum salts, developed almost a century ago, remain the most commonly used adjuvant for licensed human vaccines. Compared to more recently developed vaccine adjuvants, aluminum adjuvants such as Alhydrogel are heterogeneous in nature, consisting of 1–10 micrometer-sized aggregates of nanoparticle aluminum oxyhydroxide fibers. To determine whether the particle size and aggregated state of aluminum oxyhydroxide affects its adjuvant activity, we developed a scalable, top-down process to produce stable nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
144
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 50 publications
3
144
0
1
Order By: Relevance
“…Previous studies on modified nanoscale preparation of the alum components have been shown to have potential advantages over the traditional form of alhydrogel. 14,[24][25][26] Recently it was shown by Orr et al 27 that stable nanoparticle preparation from the conventional adjuvant alhydrogel by including a poly(acrylic acid) (PAA) polymer elicited a more robust antigen-specific Th1 immune response than alhydrogel. 27 In an attempt to improve the adjuvant characteristics of traditional aluminum hydroxide compounds, in the present study, we have prepared crystalline and amorphous forms of AH nps and evaluated its physicochemical and immunomodulating potential by utilizing antigen D4 of Bacillus anthracis.…”
Section: Figurementioning
confidence: 99%
“…Previous studies on modified nanoscale preparation of the alum components have been shown to have potential advantages over the traditional form of alhydrogel. 14,[24][25][26] Recently it was shown by Orr et al 27 that stable nanoparticle preparation from the conventional adjuvant alhydrogel by including a poly(acrylic acid) (PAA) polymer elicited a more robust antigen-specific Th1 immune response than alhydrogel. 27 In an attempt to improve the adjuvant characteristics of traditional aluminum hydroxide compounds, in the present study, we have prepared crystalline and amorphous forms of AH nps and evaluated its physicochemical and immunomodulating potential by utilizing antigen D4 of Bacillus anthracis.…”
Section: Figurementioning
confidence: 99%
“…Surprisingly, it was recently reported that injection of alum with a carefully optimized protocol and a precise vaccination time schedule, induced effective anti-tumor CTL responses showing non-specific tumor suppression [13]. These outcomes indicate that innovative strategies may remarkably improve adjuvanticity of alums and even enable the alum-adjuvanted vaccines to elicit both humoral and cellular immunity, suggesting the Al-based adjuvants of more potentials in boosting immunoresponse than those in practical use [14].…”
Section: Introductionmentioning
confidence: 99%
“…3b). Also, minimizing alum into nanoparticles remarkably enhances the VADS traffic to the draining lymph nodes, wherein different types of functional cells have an enlarged chance to be stimulated by vaccines to orchestrate to improve immunological reactions contributing to elevated immunity [14,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this, researchers are now making efforts on reformulation of conventional alums to improve their adjuvanticity. In particular, it was found that engineering of alums into special nanostructures, with/without certain materials, such as phospholipid engendering the phospholipid bilayer-coated aluminum nanoparticles (PLANs) and poly(acrylic acid) generating nanorods, can remarkably reduce their local irritating activity while rendering them able to enhance cellular immune responses toward the carried Ags [34][35][36][37][38][39]. These outcomes inspire us to trial the feasibility of using aluminum nanoparticles (ANs) as a pulmonary VADS for delivering vaccines to elicit strong mucosal immunity against air-borne pathogens, such as SARS-CoV2 and MERS, that incline to infringe and disable human respiratory system.…”
Section: Introductionmentioning
confidence: 99%